Aging-Related Alterations to Persistent Firing in the Lateral Entorhinal Cortex Contribute to Deficits in Temporal Associative Memory - Lin, Carmen; Oh, M. Matthew; Disterhoft, John F. (Frontiers in Aging Neuroscience, 2022)
With aging comes a myriad of different disorders, and cognitive decline is one of them. Studies have consistently shown a decline amongst aged subjects in their ability to acquire and maintain temporal associative memory. Defined as the memory of the association between two objects that are separated in time, temporal associative memory is dependent on neocortical structures such as the prefrontal cortex and temporal lobe structures. For this memory to be acquired, a mental trace of the first stimulus is necessary to bridge the temporal gap so the two stimuli can be properly associated. Persistent firing, the ability of the neuron to continue to fire action potentials even after the termination of a triggering stimulus, is one mechanism that is posited to support this mental trace. A recent study demonstrated a decline in persistent firing ability in pyramidal neurons of layer III of the lateral entorhinal cortex with aging, contributing to learning impairments in temporal associative memory acquisition. In this work, we explore the potential ways persistent firing in lateral entorhinal cortex (LEC) III supports temporal associative memory, and how aging may disrupt this mechanism within the temporal lobe system, resulting in impairment in this crucial behavior.